Potensi Ubi Jalar Ungu dan Kuning (Ipomoea batatas) Sebagai Terapi Penurunan Kadar Gula Darah: Potential of Purple and Yellow Sweet Potato (Ipomoea batatas) as Therapy for Lowering Blood Sugar Levels - Muhammad Sungging Pradana; Musdholifa Musdholifa; Wargianti Wargianti (YCMM, 2022)
The aim of this study was to measure the potential of purple sweet potato and yellow sweet potato (lpomoea batatas) juice in reducing blood sugar levels in mice strain BALB/c (Mus musculus) conditioned by hyperglycemia. This study was required 30 mice and divided into 3 groups placed in cages. Each groups consisted of 10 female mice (Mus musculus) weighing 25-30 g and 2.5 months. The results showed that there were differences in the value of blood sugar levels in mice. The group of normal mice, blood sugar levels did not increase or decrease, the group of mice with dextrose treatment had an increase in blood sugar values, the group of mice with dextrose treatment and sweet potato therapy had a decrease in blood sugar values. The results of statistical calculations obtained a significance value of 0.00 which means that the value of blood sugar levels has a significant difference after administration of purple sweet potato and yellow sweet potato juice. The conclusion of this study that purple and yellow sweet potatoes juice (lpomoea batatas) could lower blood sugar levels in mice (Mus musculus) which were previously hyperglicemia conditioned, so it could be continued as candidates to be tested in further research purple and yellow sweet potatoes can be candidats for blood sugar lowering foods.